Os fundamentos epistemológicos do direito no constitucionalismo contemporâneo - Abel, Henrique (Universidade do Vale do Rio dos Sinos, 2016)
The present work seeks to support the thesis that the Democratic Rule of Law, coming from Contemporary Constitutionalism, represents a new political-legal paradigm that is radically transformative in comparison with the previous incarnations of the Modern State. It argues, however, that this new political-legal paradigm was not accompanied by a new legal epistemological paradigm (although the so-called "neo-constitutionalism" represented a failed and insufficient attempt in this sense). Given the fact that the last major legal epistemology of universal influence, Kelsen's Pure Theory of Law, is today absolutely inadequate and insufficient to explain the Law within that new political-legal framework, a legal epistemological (re)construction - adequate to Contemporary Constitutionalism - is much needed. An effectively post-positivist legal epistemology, coupled with the methodological-interpretative paradigm of legal hermeneutics, must be capable of giving the conditions of discursive and scientific legitimacy for the Law, in the sense of been capable to avoid being manipulated or distorted by political or economic power. Above all, it must assure the Law's discursive autonomy necessary for it to act as a qualified instrument of concretization of the Democratic Rule of Law, protecting fundamental rights and democracy.
Keywords: Direito; Filosofia; Epistemologia jurídica; Positivismo jurídico; Constitucionalismo contemporâneo; Law; Philosophy; Legal epistemology; Legal positivism; Contemporary constitutionalism; ACCNPQ::Ciências Sociais Aplicadas::Direito